The incidence of rotavirus infection among infants and children with acute gastroenteritis - Yulidar Yulidar; Soebagyo Soebagyo; Syahrir Dollah; Iskandar Zulkarnaen; Sunyataningkamto Sunyataningkamto; Sabdo Waluyo (Paediatrica Indonesiana, 1984)
In June -July 1982, 52 infants and children ranging in age from 0-10 years who suffered from acute gastroenteritis were studied for rotavirus infection, using the Elisa method : 11.5 % were found positive. The sex incidence in rotavirus gastroenteritis was greater in males than females. The highest age incidence was over 5 years and there was no significant effect of nutritional status of the patients as jar as the incidence of infection was concerned.